MoS2-SiO2/EG hybrid nanofluid transport in a rotating channel under the influence of a strong magnetic dipole (Hall effect). Issue 6 (27th June 2020) - Mahato, N.; Banerjee, S.M.; Jana, R.N.; Das, S.
Abstract : Purpose: The article focuses on the magnetohydrodynamic (MHD) convective flow of MoS2 -SiO2 /ethylene glycol (EG) hybrid nanofluid. The effectiveness of Hall current, periodically heating wall and shape factor of nanoparticles on the magnetized flow of hybrid nanocomposite molybdenum disulfide- silicon dioxide (MoS2 -SiO2 ) suspended in ethylene glycol (EG) in a vertical rotating channel under the influence of strong magnetic dipole (Hall effect) and thermal radiation is assessed. One of the channel walls has an oscillatory temperature gradient. Four different shapes (i.e. brick, cylinder, platelet and blade) of nanoparticles disseminated in base fluid (EG) are considered for simulation of the flow. Design/methodology/approach: The analytical solution of governing equations has been presented. Influences of emerging physical parameters on the velocity and temperature profiles, the shear stresses and the rate of heat transfer are pointed out and discussed via graphs and tables. Findings: The analysis revealed that Hall parameter has suppressing behavior on the velocity profiles within the rotating channel. The impact of nanoparticle shape factor advances the temperature characteristics significantly in the rotating channel. Brick-shape nanoparticles put up relatively low-temperature distribution in the rotating channel. The Hall parameter reduces the amplitudes of the shear stresses at the channel wall. However, the radiation parameter enhances the amplitude of the rate of heat transfer at the channel wall. Social implications: The important technical advantage of hybrid composition of nanoparticles as a drug carrier is its stability, high thermal conductivity, high load carrying capacity, etc. The proposed model may be beneficial in biomedical engineering, automobile parts, mineral and cleaning oils manufacturing, rubber and plastic industries. Originality/value: To the best of our knowledge, there is little or no report on the aspects of assessment of the effectiveness of Hall current and nanoparticle shape factor on an MHD flow and heat transfer of an electrically conducting MoS2 -SiO2 /EG ethylene glycol-based hybrid nanofluid confined in a vertical channel with periodically varying wall temperature subject to a rotating frame. The present work furnishes a robust benchmark for the dynamics of nanofluids.